Duration of Unemployment Benefits and Quality of Post-Unemployment Jobs: Evidence from a Natural Experiment - van Ours, Jan C.; Vodopivec, Milan (World Bank, Washington, DC, 2012)
This paper investigates how the potential duration of unemployment benefits affects the quality of post-unemployment jobs. It takes advantage of a natural experiment introduced by a change in Slovenia's unemployment insurance law that substantially reduced the potential benefit duration. Although this reduction strongly increased job finding rates, the quality of the post-unemployment jobs remained unaffected. The paper finds that the law change had no effect on the type of contract (temporary versus permanent), the duration of the post-unemployment job, or the wage earned in the job.